2021
DOI: 10.1051/e3sconf/202125809038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cracking causes in building structural elements

Abstract: The article deals with the problems of buildings built many years ago, in which current and major repairs were not carried out in an appropriate manner. At the same time, buildings experience various deformations, such as yield, heel, subsidence, deflections, bends, twists, distortions, horizontal displacements. The survey of residential buildings built in the 80s is described and the analysis of the results of the survey of one of these buildings is carried out. The theoretical problem of the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Table 1 shows the optimal combinations of the layer thickness and the inclination angle of the nozzle axis to the surface and considers the technological schemes of deposition. An analysis of different methods showed that the most acceptable organization of the technological process of applying a mixture to a vertical surface is the method of supply using the proposed device [13][14][15]. This allows increasing labor productivity and performing work efficiently, since the work is performed by suspended equipment, and it controls the work of the operator.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Table 1 shows the optimal combinations of the layer thickness and the inclination angle of the nozzle axis to the surface and considers the technological schemes of deposition. An analysis of different methods showed that the most acceptable organization of the technological process of applying a mixture to a vertical surface is the method of supply using the proposed device [13][14][15]. This allows increasing labor productivity and performing work efficiently, since the work is performed by suspended equipment, and it controls the work of the operator.…”
Section: Research Results and Discussionmentioning
confidence: 99%